Available online Efficiency potential of indirectly heated solar reforming with different types of solar air receivers. (5th January 2016) - von Storch, Henrik; Roeb, Martin; Stadler, Hannes; Sattler, Christian; Hoffschmidt, Bernhard
Highlights: A process for indirectly heated solar reforming of natural gas with air as heat transfer fluid is proposed. Different solar receivers are modeled and implemented into the reforming process. The overall efficiency of the process with different solar receivers is determined. Optimum solar receiver characteristics for application in a solar reforming process are determined. Abstract: In solar reforming, the heating value of natural gas is increased by utilization of concentrated solar radiation. Hence, it is a process for storing solar energy in a stable and transportable form that also permits further conversion into liquid fuels like methanol. This process has the potential to significantly decrease the natural gas consumption and the associated CO2 -emissions of methanol production with only few open questions to be addressed prior to commercialization. In the medium and long term, it has the potential to generate methanol as an environmentally friendly fuel for both transport as well as flexible electricity production in combined cycle gas turbines, when biogas is used as reactant. In a previous study the high potential of indirectly heated solar reforming with solar air receivers was shown; however, the efficiency is limited when using state of the art open volumetric receivers. Therefore, different types of air receivers are implemented into an indirectly heated solar reforming process and the overall efficiency potential is assessed in the present study. The implemented receivers are an open volumetric cavity receiver, a closed volumetric cavity receiver and a tubular cavity receiver. The open volumetric cavity receiver and tubular cavity receiver achieve the best results due to their capability of operating efficiently at temperatures well above 700 °C. For these receivers peak efficiencies up to 29% and 27% respectively are predicted. As the utilization of an open volumetric cavity receiver constitutes an open heat transfer loop, the air return ratio together with air return temperature is identified as a major impact factor for overall efficiency. With an improved air return ratio, annual process efficiency of 18.4% is feasible. Considering its relative technical simplicity, this makes indirectly heated solar reforming a promising technology to efficiently provide renewable energy for methanol production and thereby diversify solar energy utilization.